Predictors of 1-year compliance with adaptive servoventilation in patients with heart failure and sleep disordered breathing: preliminary data from the ADVENT-HF trial. Issue 2 (21st February 2019) - Perger, Elisa; Lyons, Owen D.; Inami, Toru; Smith, Stephanie; Floras, John S.; Logan, Alexander G.; Bradley, T. Douglas
Despite its effectiveness in suppressing sleep disordered breathing (SDB), positive airway pressure therapy (PAP) is not always well tolerated by patients and long-term adherence can be problematic. Recently, two multicentre, randomised clinical trials (RCTs) tested the effects of PAP for patients with cardiovascular disease and co-existing SDB on morbidity and mortality with negative outcomes [1, 2]. Relatively poor adherence to PAP therapy (mean 3.7 and 3.3 h·day −1, respectively) in these two trials might have contributed to their poor results. Indeed, higher PAP use per day is associated with better clinical outcomes than lower use [3]. Adherence to sleep apnoea treatment is essential to evaluate trials involving cardiovascular end-points. In patients with heart failure and obstructive or central sleep apnoea in the ADVENT-HF trial, adherence to adaptive servoventilation was very good. http://ow.ly/5sNz30mDj2W